Gysin restriction of topological and Hodge-theoretic characteristic classes for singular spaces - Banagl, Markus (New York journal of mathematics, 2020)
We establish formulae that show how the topological characteristic L-classes of Goresky and MacPherson, as well as the Hodge-theoretic Hirzebruch type characteristic classes defined by Brasselet, Schiirmann and Yokura transform under Gysin restrictions associated to normally nonsingular embeddings of singular spaces. We find that both types of classes transform in the same manner. These results suggest a method of normally nonsingular expansions for computing the above characteristic classes. We illustrate this method by computing Goresky-MacPherson L-classes of some singular Schubert varieties.
Kein DOI vorhanden
Gesehen am 07.01.2021